Human Antimicrobial Peptide Isolated From Triatoma infestans Haemolymph, Trypanosoma cruzi-Transmitting Vector - Diniz, Laura Cristina Lima; Miranda, Antonio; da Silva Jr., Pedro Ismael (Frontiers in Cellular and Infection Microbiology, 2018)
The importance of antimicrobial peptides (AMPs) in relation to the survival of invertebrates is well known. The source and the mode of action on the insects' immune system of these molecules have been described from different perspectives. Insects produce their own AMPs as well as obtain these molecules from various sources, for example by absorption through the intestinal tract, as previously described for Boophilus microplus. Blood-sucking barber bug Triatoma infestans attracts social, economic and medical interest owing to its role in the transmission of Chagas disease. Despite new studies, descriptions of AMPs from this insect have remained elusive. Thus, the aims of this work were to characterize the antimicrobial potential of human fibrinopeptide A (FbPA) obtained from the T. infestans haemolymph and identify its natural source. Therefore, FbPA was isolated from the T. infestans haemolymph through liquid chromatography and identified by mass spectrometry. This peptide exhibited antimicrobial activity against Micrococcus luteus. Native FbPA from human blood and the synthetic FbPA also exhibited antimicrobial activity. The synthetic FbPA was conjugated with fluorescein isothiocyanate and offered to the insects. The haemolymph collected after 72 h exhibited fluorescence at the same wavelength as fluorescein isothiocyanate. Our experiments show that beyond intrinsic AMP production, T. infestans is able to co-opt molecules via internalization and may use them as AMPs for protection.